2016
DOI: 10.3389/fpsyt.2016.00133
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transcranial Magnetic Stimulation of the Prefrontal Cortex Reduces Cocaine Intake: A Pilot Study

Abstract: BackgroundChronic cocaine consumption is associated with a decrease in mesolimbic dopamine transmission that maintains drug intake. transcranial magnetic stimulation (TMS) is gaining reliability, a useful therapeutic tool in drug addiction, since it can modulate cortico-limbic activity resulting in reduction of drug craving.AimsIn the present study, we investigated the therapeutic effect of bilateral TMS of prefrontal cortex (PFC) in reducing cocaine intake, in a sample of treatment-seeking patients with curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
(50 reference statements)
3
67
0
Order By: Relevance
“…Four studies investigated the effects of rTMS on craving for cocaine in dependent adult participants. The number of treatment sessions ranged from 1 to 12, with a frequency range between 5 and 20 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies investigated the effects of rTMS on craving for cocaine in dependent adult participants. The number of treatment sessions ranged from 1 to 12, with a frequency range between 5 and 20 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The number of treatment sessions ranged from 1 to 12, with a frequency range between 5 and 20 Hz. Three of these studies demonstrated positive results, with a significant reduction in craving for cocaine, with the exception of Bolloni et al who found no significant change in craving compared to sham, although long‐term reduction in consumption was significant when considering time as a factor.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this idea preexisting hyperexcitability of prefrontal and ventral striatum neurons in Tmod2 mutants could actively resist the cocaine-induced depression of these regions, thereby masking the maladaptive behavioral effects of cocaine 104,105 . Interestingly, high frequency (5-20 hz) transcranial magnetic stimulation that increases cortical excitability has been shown to be an effective treatment for cocaine craving [106][107][108] , indicating that cortical excitability in naive Tmod2 KO could interfere and prevent cocaine-induced addiction behavior. Basal and cocaine-induced changes in synaptic properties of accumbens neurons are also distinct from their WT counterparts and support behavioral results.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sessions of high-frequency rTMS of the left DLPFC were reported to reduce spontaneous craving for cocaine and increased the abstinence rates, as assessed by the number of cocainefree drug tests (Terraneo et al 2016). Further pilot clinical studies report that rTMS of the left DLPFC is effective in reducing craving and intake (Politi et al 2008;Bolloni et al 2016;Rapinesi et al 2016). As mentioned earlier, the mechanisms by which rTMS of DLPFC is potentially useful for reducing symptoms related to cocaine addiction are linked to the modulatory effects on neurotransmitter systems (Volkow et al 2004;Diana et al 2017).…”
Section: Evidence From Human Studiesmentioning
confidence: 91%